Applications of Knowledge Processes Among Faculty of Physical Education and Sports Sciences Professors at Kirkuk University - Diyar Karim Negm Shwani; Ali Burhan Hawar; Wadie Yassin Al-Tikriti (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
The current research aims to evaluate application of knowledge processes among faculty members at Faculty of Physical Education and Sports Sciences, University of Kirkuk, and to identify differences in mean among research sample and the hypothetical mean for scale's axes, as well as to determine the ordinal ranking of the research axes. The researchers hypothesize that faculty members at Faculty of Physical Education and Sports Sciences, University of Kirkuk, possess a good level of effectiveness in applying knowledge processes, that there are statistically significant differences between mean of research sample and hypothetical mean for scale's axes, and that there is a variation in ordinal ranking of research axes. The researchers used descriptive method as it is suitable for nature of research. The research sample consisted of (16) faculty members, and data were statistically analyzed using unclear possibly statistics. The hypothetical mean, standard deviation, one-sample t-test, percentile weight, and percentage were used. The researchers concluded that research sample achieved a high level in assessments of knowledge acquisition and generation processes across four research axes: knowledge acquisition and generation, knowledge storage, knowledge distribution, and knowledge application. All items on scale achieved required scores. Knowledge management processes demonstrated positive levels exceeding theoretical hypothetical mean for statements. The means for all axes of knowledge management processes scale exceeded hypothetical means for those axes. Significant differences were found among means for all four axes of Knowledge, Management, Processes scale and hypothetical means for those axes, favoring research sample. The knowledge acquisition and distribution axis ranked first, Knowledge distribution axis second, Knowledge Storage axis third, fourth focus is on knowledge application.